2013
DOI: 10.1177/0013161x13492797
|View full text |Cite
|
Sign up to set email alerts
|

How School and District Leaders Support Classroom Teachers’ Work With English Language Learners

Abstract: Purpose: This study examines the ways in which school and district leaders create systems of support for classroom teachers who work with linguistically diverse students. We attempt to uncover the intentional supports leaders put in place for classroom teachers and how this may be part of a broader teaching and learning effort. Research Design: Through a qualitative case study of four districts serving different populations of English Learner (EL) students, we examine school and district leadership actions aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…Students learn a second language through a long process that cultivates academic English proficiency over a four to seven-year period (Cummins, 1981). Supporting Latina/o emergent bilinguals requires that teachers and principals have access to extensive professional development and ongoing coaching that can perhaps only come through a long-term district-wide improvement process (Cheung & Slavin, 2012;Elfers & Stritikus, 2014). The role of the superintendent is therefore critical, given their positional authority to envision and make such investments at the district level.…”
Section: Introductionmentioning
confidence: 99%
“…Students learn a second language through a long process that cultivates academic English proficiency over a four to seven-year period (Cummins, 1981). Supporting Latina/o emergent bilinguals requires that teachers and principals have access to extensive professional development and ongoing coaching that can perhaps only come through a long-term district-wide improvement process (Cheung & Slavin, 2012;Elfers & Stritikus, 2014). The role of the superintendent is therefore critical, given their positional authority to envision and make such investments at the district level.…”
Section: Introductionmentioning
confidence: 99%
“…An important consideration when examining teaching practices aimed at serving ELLs is that ELL students come to school with a wide range of native language and English language literacy habits and skills, uneven content-area backgrounds, and vastly different family and schooling experiences (Elfers & Stritikus, 2014). Elfers and Stritikus (2014) concluded that the issues that arise from studying instruction for ELLs include the challenge of advanced academic achievement and attention to the sociocultural dimensions of the schooling experience.…”
Section: Inclusion Of Ells In the Mainstream Classroommentioning
confidence: 99%
“…Elfers and Stritikus (2014) concluded that the issues that arise from studying instruction for ELLs include the challenge of advanced academic achievement and attention to the sociocultural dimensions of the schooling experience. In-depth studies by Collier (1987) and August and Hakuta (1997) focused on students who were literate or had deep content knowledge in their native language and concluded that those students are more likely to succeed in academic performance when compared to those who do not have these skills.…”
Section: Inclusion Of Ells In the Mainstream Classroommentioning
confidence: 99%
See 2 more Smart Citations